Analisis Manajemen Risiko Keselamatan di Perusahaan Kontraktor Pertambangan Batubara Site XYZ Berdasarkan Sistem Manajemen Keselamatan Pertambangan Mineral dan Batubara - Astien Setianingrum; Indri Hapsari Susilowati (Pro Health Jurnal Ilmiah Kesehatan, 2020)
Risk management is a process of managing risk so the organization can achieve its goals. A strong fundamental is necessary for understanding the concept of risk management before it is implemented. This study will analyze mining safety risk management at PT HPU site XYZ based on the Mineral and Coal Mine Safety Management System (SMKP Minerba). This research is a qualitative descriptive study . Data retrieval is done through in-depth interviews and document review (documentation) with key informants, namely, 4 Project Managers, 14 Superintendents, and 18 Foreman.The results of the interviews were analyzed by its content and compared to PT HPU documents based on Mineral and Coal Mining Safety Management System (SMKP Minerba) and also other risk management standards (ISO 31000: 2009, AS / NZS 4360: 2004, and ISO 45001: 2018) for additional reference. Based on content analysis, it was found that the supervisor's interpretation of PT HPU regarding risk management was not fully in accordance with risk management standards since the company's procedures had not accommodated the entire risk management process. Therefore, it is necessary to formulate procedures for risk management that are integrated with the company's mining safety management system and understood by each line of management.